Psychotic symptoms in borderline personality disorder: developmental aspects - Cavelti, Marialuisa; Thompson, Katherine; Chanen, Andrew M.; Kaess, Michael (Current opinion in psychology, 2021)
Even though the borderline concept has historically been intertwined with psychosis, psychotic symptoms in people with borderline personality disorder (BPD) have long been marginalized as somehow not real, transient, or ‘pseudo’ in nature. Dispelling this myth, we summarize recent research indicating that (a) psychotic symptoms in general and auditory verbal hallucinations in particular in people with BPD show more similarities than differences with those symptoms in people with psychotic disorders, and (b) that the co-occurrence of BPD and psychotic symptoms is a marker of severe psychopathology and of risk for poor outcome (e.g. suicidality). We propose the period from puberty to the mid-20s, when both BPD and psychotic features usually emerge for the first time, constitutes a critical time window for early intervention to prevent the development of severe mental disorders in the future. Implications for the treatment of psychotic symptoms in BPD and future research directions in this field are discussed.
Gesehen am 26.06.2021
Publikationsdatum online: 12th July 2020